Two novel antithetical KN blood group antigens may contribute to more than a quarter of all KN antisera in Europe - Grüger, Daniela; Zeretzke, Anja; Habicht, Cora P.; Skaik, Younis; Wagner, Franz F.; Scharberg, Erwin; Costelloe, Aisling; Martens, Jörg; Verboom, Murielle; Bugert, Peter; Schneeweiss, Clemens (Immunohematology, 2020)
Background All antigens described in the KN blood group system are located in the long homologous repeat D (LHR-D) of complement receptor 1 (CR1). While there have been reports that some sera react only with the long homologous repeat C (LHR-C), the antigens in LHR-C are unknown. Study Design and Methods Recombinant LHR-C and LHR-D were used to identify antibodies directed against LHR-C of CR1, into which a point mutation was introduced to characterize the underlying blood group antigens. In addition, database studies to define haplotypes of CR1 were performed. Results Several antisera were identified that were specific against CR1 p.1208His and against CR1 p.1208Arg, located in LHR-C. Fifteen KN haplotypes were found in the Ensembl genome browser. It was shown that due to a linkage disequilibrium anti-CR1 p.1208His may be mistaken for anti-KCAM. Conclusion A novel antithetical KN blood group antigen pair was found at position p.1208 of CR1, for which the names DACY and YCAD are proposed. Antibodies against these two novel antigens seem to contribute to more than a quarter of all KN sera in Europe.
Gesehen am 13.01.2026